Novel low cost synchronisation network for spread spectrum systems - Van de Groenendaal, Joannes Gerard (Department of Electrical Engineering, 2016)
Spread Spectrum systems are found in many flavours, used in many applications and have existed since the early days of radio communications. The properties of spread spectrum do however place restrictions on the design, and often make the implementation expensive and complex. When using spread spectrum to provide a basic communications infrastructure, many factors need to be considered. These include supplying the appropriate technology at the right cost. To achieve this a trade-off against performance is often required. One of the more difficult aspects of Spread Spectrum design is the synchronisation of the spreading waveform. The primary characteristic of pseudonoise sequence synchronisation is the need for two levels of synchronisation namely acquisition (course synchronisation) and tracking (fine synchronisation). In these networks (the term network is used to describe a circuit or system throughout the thesis.) a decision is required to switch between the two synchronisation modes. The two layer structure of the typical pseudonoise sequence synchronisation network can increase the overall cost of spread spectrum systems. The objective of the research was therefore to find solutions to reduce the overall cost and complexity of the synchronisation network. The synchronisation structure should perform acquisition and tracking in a single structure, and thereby be low cost. To achieve the primary objective of this dissertation a. mixture of theory, simulations and practical implementation was used. The basis of the investigation was a time-variant spectral evaluation of pseudonoise sequences. It is shown that by multiplying a differentiated pseudonoise sequence with another pseudonoise sequence, useful information is obtained that can form the basis of a synchronisation network.